Assessment of drip and flood irrigation on biomass production, nutrient content and water use efficiency of maize (Zea mays L.) (Dhaka University Journal of Biological Sciences, 2013)
An experiment was conducted in wooden boxes to assess flood, surface and sub-surface drip irrigation on biomass production, nutrient content and water use efficiency of maize (Zea mays L.). Four levels of irrigation treatments were applied: (i) SD1 = Drip irrigation pipe was set up on the surface of the soil ; (ii) SSD2 = Drip irrigation pipe was buried up to 5 cm depth; (iii) SSD3 = Drip irrigation pipe was buried up to 7.5 cm depth and (iv) FI = Flood irrigation was practiced without any drip irrigation pipe. Leaf area, leaf area index and biomass production of maize were significantly (p < 0.05) higher in SSD3 than SSD2 and FI treatments. Biomass production was 37.2, 41.1, 54.2 and 35.2 g in SD1, SSD2, SSD3 and FI treatments, respectively. Water use efficiency (WUE) was also significantly (p < 0.05) higher in surface and sub-surface drip irrigation than flood irrigation. Values for WUEs were 0.248, 0.298, 0.430 and 0.156 kg/m3 in SD1, SSD2, SSD3 and FI treatments, respectively. As a result, all three drip irrigation treatments enhanced water use efficiencies than flood irrigation. Comparing the three drip irrigation treatments, significantly (p < 0.05) higher nitrogen was found both in leaf and stem (3.3 and 3.8%) in sub-surface drip irrigation at 7.5 cm depth than flood irrigation (2.2 and 1.4%). Although, potassium contents in leaf and stem were not significantly different between the treatments, but had a tendency to be higher in drip irrigation treatments. Above all, drip irrigation performed better with higher water use efficiency.Dhaka Univ. J. Biol. Sci. 22(1): 47-54, 2013 (January)